Idenitification and characterization of protease encoding genes from metagenomic library of dairy effluent - Roshan Lal (Department of Plant Biotechnolog, College of Agriculturey, 2016)
The study entitled “Identification and characterization of protease encoding genes from metagenomic library constructed from dairy effluent”, was carried out at the Department of Plant Biotechnology, College of Agriculture, Vellayani during 2014-2015. The objective of the study was to construct metagenomic library from dairy effluent and to identify and characterize novel protease encoding genes. The dairy effluent was collected from the effluent outlet of MILMA unit, Ambalathara, Thiruvananthapuram. Metagenomic DNA was isolated and purified, which showed a size above 48.5 kb on agarose gel. The concentration was 2.8μg/μl and A 260 /A 280 value was 1.81 The metagenomic DNA was digested with the restriction enzyme Hpa I (Haemophilus parainfluenzae I). Digests obtained after 1h (fragment size higher than 48 kb) and 2h (fragment smaller than 33.5 kb) were cloned into pEZ BAC vector using clone smart ligase of Lucigen (USA). Transformed cells were selected by blue white screening on chloramphenicol (25μg/ml) containing plates. Functional screening of library on skimmed milk agar identified a clone with protease activity. The plasmid DNA isolated from the protease positive clone on agarose gel showed a band of size bigger than 10kb, compared to control (7.2kb), showing successful insertion of the metagenomic fragment. The vector isolated from the positive clone when digested with HpaI showed an extra band of size 9kb, confirming the presence of insert. The protease activity of the crude enzyme extract of this clone at 24 th h of growth was 166.99U/ml (111.32U/mg protein). The enzyme showed maximum stability at pH 9.0 and at a temperature 40 0 C. Enzyme incubated in 5% SDS for 1h retained only 10.75% of the original activity. The PCR amplification of metagenome using universal primer for 16S rRNA gene yielded a product of size 140 bp length. The blast analysis of the sequence revealed similarity with Enterobactor asburisestrain 35734 andKlebsiella pneumonia with E value 3e-50.